Do People Value More Informative News? - Felix Chopra; Ingar K. Haaland; Christopher Roth (Center for Economic Studies and ifo Institute (CESifo), 2019)
We examine whether the desire for more information is people's dominant motive for reading economic and political news. Drawing on representative samples of the U.S. population with more than 15,000 respondents in total, we measure and experimentally vary people's beliefs about the informativeness of news. Inconsistent with the desire for more information being the dominant motive for people's news consumption, treated respondents who think that a newspaper is less likely to suppress information reduce their demand for news from this newspaper. Furthermore, treated respondents who think that a news outlet is more likely to make false claims do not reduce their demand for this outlet. These findings strongly suggest that people have other motives to read news that sometimes conflict with their desire for more informative news. We discuss the implications of our findings for the regulation of media markets.
Keywords: D83; D91; L82; 330; news consumption; information; media bias; belief polarization; informativeness